Superconductivity in LiGa2Ir Heusler type compound with VEC = 16 - Karolina Górnicka (Nature Portfolio, 2021)
Abstract Polycrystalline LiGa2Ir has been prepared by a solid state reaction method. A Rietveld refinement of powder x-ray diffraction data confirms a previously reported Heusler-type crystal structure (space group Fm-3m, No. 225) with lattice parameter a = 6.0322(1) Å. The normal and superconducting state properties were studied by magnetic susceptibility, heat capacity, and electrical resistivity techniques. A bulk superconductivity with Tc = 2.94 K was confirmed by detailed heat capacity studies. The measurements indicate that LiGa2Ir is a weak-coupling type-II superconductor ( $${\uplambda }$$ λ e–p = 0.57, $${Δ }$$ Δ C/ $${\upgamma }$$ γ Tc = 1.4). Electronic structure, lattice dynamics, and the electron–phonon interaction are studied from first principles calculations. Ir and two Ga atoms equally contribute to the Fermi surface with a minor contribution from Li. The phonon spectrum contains separated high frequency Li modes, which are seen clearly as an Einstein-like contribution in the specific heat. The calculated electron–phonon coupling constant $${\uplambda }$$ λ e–p = 0.68 confirms the electron–phonon mechanism for the superconductivity. LiGa2Ir and recently reported isoelectronic LiGa2Rh are the only two known representatives of the Heusler superconductors with the valence electron count VEC = 16.